2021
DOI: 10.1177/1179173x20988674
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Enigma in Coronavirus Disease 2019: A Tug of War between Predisposition and Possible Way Out

Abstract: Background: The recent global inclination for smoking during the Coronavirus Disease 2019 (COVID-19) pandemic has drawn attention to the impact of smoking on COVID-19. While smoking increases susceptibility to common respiratory pathogens including the closely related coronaviruses, COVID-19 causing Severe Acute Respiratory Coronavirus 2 (SARS-CoV-2) being a respiratory pathogen intrigues the possible association between smoking and viral pathogenicity. Smoking and COVID-19: The gender dependence of COVID-19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…As already reported in several studies, we found a lower risk of seropositivity among active smokers [31,33,47,48], as well as lower levels of IgG among seropositive current smokers; conversely, we observed a higher risk of seropositivity among former smokers compared to never smokers. Some hypotheses have been put forward to explain the apparent lower incidence of SARS-COV-2 infection among active smokers [47,49,50], including a downregulation caused by nicotine on Interleukin-6 (IL-6), which plays a role in COVID-19 severity and interferes with the Angiotensin-Converting Enzyme 2, or an increased concentration of nitric oxide in the respiratory tract that could alter virus replication. However, until robust evidence from further investigations of the interaction between smoking and SARS-COV-2 infection becomes available, public health recommendations other than smoking banning cannot be proposed [49].…”
Section: Discussionmentioning
confidence: 99%
“…As already reported in several studies, we found a lower risk of seropositivity among active smokers [31,33,47,48], as well as lower levels of IgG among seropositive current smokers; conversely, we observed a higher risk of seropositivity among former smokers compared to never smokers. Some hypotheses have been put forward to explain the apparent lower incidence of SARS-COV-2 infection among active smokers [47,49,50], including a downregulation caused by nicotine on Interleukin-6 (IL-6), which plays a role in COVID-19 severity and interferes with the Angiotensin-Converting Enzyme 2, or an increased concentration of nitric oxide in the respiratory tract that could alter virus replication. However, until robust evidence from further investigations of the interaction between smoking and SARS-COV-2 infection becomes available, public health recommendations other than smoking banning cannot be proposed [49].…”
Section: Discussionmentioning
confidence: 99%
“…Despite its well-known health risks, smoking and excessive drinking are still major current public health issues worldwide (Rakhi and Biswas, 2021;Simpson et al, 2019;Strebel and Terry, 2021). Indeed, smoking and excessive drinking account for several public policy consequences (e.g., passive smoking, road accidents, domestic violence) along with elevated public healthcare costs estimated at US$ 1.4 trillion per year for the global economy (WHO, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its well-known health risks, smoking and excessive drinking are still major current public health issues worldwide (Rakhi and Biswas, 2021; Simpson et al , 2019; Strebel and Terry, 2021). Indeed, smoking and excessive drinking account for several public policy consequences (e.g.…”
Section: Introductionmentioning
confidence: 99%